Literatos en 90 minutos. - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (90 minutos., 2017)
The Pack Literatos 1 collection brings together 6 of the twentieth century literati who changed, among others, literature.